1999
DOI: 10.1200/jco.1999.17.2.668
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of K-ras Codon 12 Mutations in Patients With Resected Stage I and II Non–Small-Cell Lung Cancer

Abstract: Codon 12 K-ras mutations were more common in adenocarcinomas than in squamous cell carcinomas. For the subgroup with stage II NSCLC, there was a statistically significant adverse effect on survival for the presence of K-ras mutations. However, when the entire group was considered, the presence of K-ras mutations was not of prognostic significance in this cohort of patients with resected early-stage NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(67 citation statements)
references
References 23 publications
1
60
0
6
Order By: Relevance
“…In total, 53 publications, published between 1990 and 2003, were found eligible for the systematic review (Rodenhuis et al, 1988(Rodenhuis et al, , 1997Slebos et al, 1990;Mitsudomi et al, 1991;Miyamoto et al, 1991;Harada et al, 1992;Sugio et al, 1992;Rosell et al, 1993Rosell et al, , 1995bRosell et al, , 1996Rosell et al, , 1997Volm et al, 1993Volm et al, , 2002Westra et al, 1993;Kern et al, 1994;Li et al, 1994;Silini et al, 1994;Fujino et al, 1995;Kashii et al, 1995;Keohavong et al, 1996Keohavong et al, , 1997Cho et al, 1997;Dosaka-Akita et al, 1997;Fukuyama et al, 1997;Komiya et al, 1997;Pifarré et al, 1997;Siegfried et al, 1997;Visscher et al, 1997;De Gregorio et al, 1998;Greatens et al, 1998;Huang et al, 1998;Kim et al, 1998;Kwiatkowski et al, 1998;Nemunaitis et al, 1998;Wang et al, 1998;Dingemans et al, 1999;Fu et al, 1999;Graziano et al, 1999;Miyake et al, 1999;Nelson et al, 1999;Hommura et al, 2000;…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In total, 53 publications, published between 1990 and 2003, were found eligible for the systematic review (Rodenhuis et al, 1988(Rodenhuis et al, , 1997Slebos et al, 1990;Mitsudomi et al, 1991;Miyamoto et al, 1991;Harada et al, 1992;Sugio et al, 1992;Rosell et al, 1993Rosell et al, , 1995bRosell et al, , 1996Rosell et al, , 1997Volm et al, 1993Volm et al, , 2002Westra et al, 1993;Kern et al, 1994;Li et al, 1994;Silini et al, 1994;Fujino et al, 1995;Kashii et al, 1995;Keohavong et al, 1996Keohavong et al, , 1997Cho et al, 1997;Dosaka-Akita et al, 1997;Fukuyama et al, 1997;Komiya et al, 1997;Pifarré et al, 1997;Siegfried et al, 1997;Visscher et al, 1997;De Gregorio et al, 1998;Greatens et al, 1998;Huang et al, 1998;Kim et al, 1998;Kwiatkowski et al, 1998;Nemunaitis et al, 1998;Wang et al, 1998;Dingemans et al, 1999;Fu et al, 1999;Graziano et al, 1999;Miyake et al, 1999;Nelson et al, 1999;Hommura et al, 2000;…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…According to the hypothesis that NSCLC-ND may share clinical behavior and therapy responsiveness with SCLC, which is the prototype of highly malignant and therapy-sensitive NE tumors of the lung, several studies 18 have correlated NSCLC-ND with shorter survival, more advanced disease stage, and/or increased chemosensitivity. 19 -31 Other investigators, however, have failed to show any correlation between NE differentiation and prognosis or susceptibility to the therapy 28,[32][33][34][35][36][37][38][39][40] or even have reported better survival rates for patients with NSCLC-ND. 24,37,38,41 Differences in tissue processing, techniques or markers used for highlighting NE differentiation, definitions of positive results, and study population selection may account for these contradictory results reported in the clinical meaning of NE differentiation in patients with NSCLC.…”
mentioning
confidence: 99%
“…Currently, there are numerous immunomarkers used to detect bronchopulmonary neuroendocrine tumors, most commonly neuron-specific enolase, synaptophysin and chromogranin A, although each has a different sensitivity and specificity (9). Therefore, searching for the best panel of immunomarkers to detect the differentiation of neuroendocrine tumors is crucial.…”
Section: Discussionmentioning
confidence: 99%